The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.14715/cmb/2017.63.10.20
|View full text |Cite
|
Sign up to set email alerts
|

The association between murine double minute 2 (MDM2) rs2279744 and endometrial cancer risk in a Chinese Han population

Abstract: Some studies investigated the association between the murine double minute 2 (MDM2) rs2279744 polymorphism and endometrial cancer susceptibility, but provided controversial or inconclusive results. Thus, we decided to perform this case-control study to determine the association between MDM2 rs2279744 polymorphism and endometrial cancer in a Chinese Han population. A total of 215 endometrial cancer patients and 212 cancer-free controls were included in this case-control study. We genotyped the MDM2 rs2279744 po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The MDM2 protein is overexpressed in both primary and metastatic EC, which also indicates that MDM2 protein expression is closely associated with the development of EC (50). In addition, Wu and Luo (51) revealed that the MDM2 rs2279744 polymorphism was significantly associated with EC risk in the Chinese Han population.…”
Section: Discussionmentioning
confidence: 99%
“…The MDM2 protein is overexpressed in both primary and metastatic EC, which also indicates that MDM2 protein expression is closely associated with the development of EC (50). In addition, Wu and Luo (51) revealed that the MDM2 rs2279744 polymorphism was significantly associated with EC risk in the Chinese Han population.…”
Section: Discussionmentioning
confidence: 99%